Effects of Zinc Oxide Nanoparticles on the Properties of Pectin/Alginate Edible Films - Thi Minh Phuong Ngo (2018)
© 2018 Thi Minh Phuong Ngo et al. This study aimed at developing the functional packaging properties of pectin/alginate films by adding zinc oxide nanoparticles (ZnO-NPs). The ZnO-NPs were added to the pectin/alginate film at the concentrations of 0.5, 2.5, 5, and 25 g/100 g of blended polymer. The effects of the ZnO-NP incorporation on the mechanical properties, hydration properties, oxygen permeability, ultraviolet transmission, transparency, and antimicrobial activity of the films were investigated. The addition of ZnO-NPs from 0 to 5 g/100 g of blended polymer to the pectin/alginate film increased 191.4% of the tensile strength, 169.8% of elongation at break, and antimicrobial properties (against Aspergillus Niger, Colletotrichum gloeosporioides, Escherichia coli, and Saccharomyces cerevisiae). In contrast, it reduced the solubility from 30.38% to 22.49%, water vapor permeability from 1.01 × 10-14 to 0.414 × 10-14 kg·m/m2·Pa·s, moisture absorption, ultraviolet light transmission, and oxygen permeability from 270.86 × 10-19 to 110.79 × 10-19 kg·m/m2·Pa·s. The effects are the highest when the concentration of the ZnO-NPs in the film was 5 g/100 g of blended polymer. Attenuated total reflectance-Fourier transform infrared analysis indicated that some interactions between the ZnO-NPs and pectin/alginate matrices were formed. These results suggest that pectin/alginate/ZnO-NPs films can be used as active packaging for food preservation.